(untitled) (Global Journal of Computer Science and Technology, 2023)
Artificial Intelligence AI refers to the simulation of human intelligence in machines that are programmed to think and mimic human cognitive processes It includes a wide range of tools that enable machines to carry out operations that otherwise need human intelligence Learning logical thinking problem-solving perception speech recognition and language understanding are some of these tasks One of the key areas where AI will have a profound effect is education Both students and teachers benefit from enhanced educational experiences because of AI It offers a personalized learning experience Although AI in education hasn t received much attention over the years understanding its concepts functions methodology and applications would provide the groundwork for the development of the education sector